Cranial bones and atlas of titanosaurs (Dinosauria, Sauropoda) from Late Cretaceous (Bauru Group) of Uberaba, Minas Gerais State, Brazil. (August 2015) - Martinelli, Agustín G.; Marinho, Thiago da Silva; Filippi, Leonardo S.; Ribeiro, Luiz Carlos Borges; Ferraz, Mara Lúcia da Fonseca; Cavellani, Camila Lourencini; Teixeira, Vicente de Paula Antunes
Abstract: Isolated left prefrontal, left squamosal and atlas of titanosaur dinosaurs are described and compared. They come from the Late Cretaceous Serra da Galga Member of the Marília Formation at the Serra do Veadinho region, Peirópolis (Uberaba County, Minas Gerais State, Brazil). Due to the sparse cranial elements of titanosaurs already known from Brazil, these specimens are noticeable to be presented. In addition, the atlas vertebra is described for the first time for Brazilian titanosaurs. The morphology of the cranial bones closely resembles lithostratian titanosaurs, such as Rapetosaurus, rather than basal titanosaurs. The atlas is similar to that of other titanosaurs, suggesting that the anatomy of this element seems to be more conservative than other vertebral elements, in which vertebral laminae play an important rule in titanosaur taxonomy. Highlights: First cranial bones and atlas vertebra of titanosaurs from Peirópolis (Minas Gerais State, Brazil). Cranial bones reminiscent of derived lithostratian titanosaurs. Atlas vertebra possible constitutes a more conservative morphology than other vertebral elements.